2018
DOI: 10.3389/fmars.2018.00327
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Diatom—Dinoflagellate Dominance During Spring Bloom in the Baltic Sea and its Potential Effects on Biogeochemical Cycling

Abstract: The Baltic Sea is affected by a range of human induced environmental pressures such as eutrophication. Here we synthesize the ongoing shift from diatom dominance toward more dinoflagellates in parts of the Baltic Sea during the spring bloom and its potential effects on biogeochemical cycling of key elements (e.g., C, N, and P). The spring bloom is the period with the highest annual primary production and sinking of organic matter to the sediment. The fate of this organic matter is a key driver for material flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 158 publications
4
94
0
Order By: Relevance
“…Long-term field investigations have revealed that Prorocentrum donghaiense, Heterosigma akashiwo, and other phytoplankton species cause extensive blooms from spring to early summer in this area (7,36,37). Similar bloom events and distinct ecological niches of these HAB species have also been reported in other coastal areas (38)(39)(40)(41). However, the mechanisms that drive bloom occurrence of different phytoplankton species are unclear.…”
supporting
confidence: 54%
“…Long-term field investigations have revealed that Prorocentrum donghaiense, Heterosigma akashiwo, and other phytoplankton species cause extensive blooms from spring to early summer in this area (7,36,37). Similar bloom events and distinct ecological niches of these HAB species have also been reported in other coastal areas (38)(39)(40)(41). However, the mechanisms that drive bloom occurrence of different phytoplankton species are unclear.…”
supporting
confidence: 54%
“…Third, if climate becomes more cloudy and windy this could effectively delay the spring bloom, and thus increase the phytoplankton-zooplankton overlap period. A lower energy input to the benthic system would reasonably reduce benthic production above the halocline, but cause less pressure on benthic oxygen consumption and potentially decreasing anoxic zones (Spilling et al, 2018). However, higher water temperatures have been suggested to increase the oxygen consumption and anoxia below the halocline (Kabel et al, 2012;Meier et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…during P 2 suggested a nutrient depletion condition or a change in nutrient supply ratios. Also, as mixotrophic dinoflagellates were known to outcompete diatoms in organic nutrient conditions (Spilling et al, 2018), the change observed within the community may also suggest the impact of organic matter input from the Eygoutier River. It is interesting to note that such hypothesis contrast with the few available studies investigating the impact of freshwater runoff on phytoplankton communities in coastal northwestern subbasin due to specific trophic state conditions.…”
Section: Impacts On Diatom Communitymentioning
confidence: 99%